Nietzsche e as implicações do Niilismo para uma releitura do cristianismo e da prática de Jesus - Gomes, Roberto dos Santos (Universidade do Vale do Rio dos Sinos, 2019)
In order to evaluate the implications that nihilism has induced for a particular way of life of Christianity that comes from the practice of Jesus, the present research aims to describe the ideal nihilistic human being that becomes mass of herd, leaves aside the certainty of the perpetuation of life and holds on to absolute truths; characterize an outspread and systematization in the organization of reason as a religious experience of the psychological necessity of an ultimate sense; Identify the ideal Christian life of Platonic-Jewish roots that moves away from Jesus-type praxis and experiences the consummation of nihilism from the hypothesis of three Christianity: 1- The Jesus of practice is: the Nietzschean psychological Jesus; he is the last Christian, and he died on the cross. 2- Christianity which borns from the Cross- (Apostles); 3- Christianity of the systematization of faith (dogmas).In which of these ways is it possible to bet on a Nietzschean approach to life affirmation?
Keywords: Niilismo; Cristianismo; Prática; Jesus; Nihilism; Christianity; Practice; Jesus; ACCNPQ::Ciências Humanas::Filosofia